THE REPRESENTATION OF LOCAL CULTURE IN INDONESIAN EFL TEXTBOOKS: RATIONALES AND IMPLICATIONS - Yogi Saputra Mahmud (University of Kuningan, 2019)
This article discusses the representation of local culture in EFL Junior High School textbooks in Indonesia. The two primary objectives of this paper are: 1) to reveal the primary reasons of incorporating local culture in EFL textbooks, and 2) to suggest further implications in responding to the incorporation of local culture in EFL textbooks. The discussion begins with the current EFL context in Indonesia with the emphasis on the considerable changes of the curriculum implementation in the Indonesian context, in which it attempts to reveal the representation of local culture implied within the 2013 curriculum. As its main arguments, this article argues that there are two predominant reasons for representing local culture in the EFL Junior High School textbooks in Indonesia which include promoting the sense of familiarity to Junior High School students in learning English as well as strengthening the aspects of national culture and identity portrayed in the textbooks. Furthermore, this article also discusses the future implications in responding to the representation of local culture in EFL Junior High School textbooks in Indonesia, including the needs to enhance the role of teachers as well as the importance of incorporating more diverse cultural representation in the textbooks.